KOMUNIKASI KELOMPOK DALAM MENUMBUHKAN RASA SOLIDARITAS DAN LOYALITAS (ANALISIS STUDI KASUS: KELOMPOK SUPORTER JAKMANIA GARIS KERAS) - Adi Hidayat (2021)
Jakmania is the designation for the supporters of a football team that is Persija Jakarta origin. Since its inception in 1997, Jakmania have increased the number of members. No wonder if Jakmania become one of the biggest supporters in Indonesia. Jakmania is always a topic of conversation when the Persija team competes, both news about riots and positive things. As a militant, solid, and loyal supporter, Jakmania often experiences friction with other groups but also often gets awards or records as the largest audience every year. Jakmania itself is an organized supporter, in which there are many groups called Koordinator Wilayah (korwil). Within the group there is one group that has high cohesiveness, its members are known to be militant, solid, and loyal, the group is Jakmania Garis Keras. This research was conducted to see the formation of Jakmania Garis Keras cohesiveness from a communication point of view. The purpose of this study is to reveal the pattern of group communication that is carried out to form a solid and loyal group. This research is based on the theory of cohesiveness, the method used is a qualitative case study to obtain actual results from informants consisting of the founder, chairman, members of the Jakmania Garis Keras and informants from academics for confirmation. The results of this study indicate that Jakmania Garis Keras always applies good and intensive communication, has a GK Camp and the concept of Imama which helps form groups that have high cohesiveness, but there is a negative impact from a cohesive group, namely the existence of group thinking or a decrease in the critical level of its members.